2021
DOI: 10.1002/aesr.202000071
|View full text |Cite
|
Sign up to set email alerts
|

Earth‐Abundant Amorphous Electrocatalysts for Electrochemical Hydrogen Production: A Review

Abstract: Electrochemical water splitting provides a promising approach to store renewable electricity in the form of hydrogen on a grand scale. However, the current techniques for large‐scale electrochemical hydrogen production rely on the use of expensive and scarce noble‐metal catalysts making it uncompetitive to traditional methods using fossil fuels. Thus, replacing noble‐metal electrocatalysts with cheap materials made of abundant elements holds the key to achieve the cost‐effectiveness. Recently, amorphous electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 223 publications
(332 reference statements)
2
33
0
Order By: Relevance
“…In addition, abundant defects in amorphous materials can improve the diffusion property that facilitates the transportation of reactants and products ( Zhai et al, 2021 ). Moreover, amorphous materials have higher structural flexibility through facile morphology engineering ( Zhang D et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, abundant defects in amorphous materials can improve the diffusion property that facilitates the transportation of reactants and products ( Zhai et al, 2021 ). Moreover, amorphous materials have higher structural flexibility through facile morphology engineering ( Zhang D et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its working principles and some of the most recent scientific developments are reviewed in detail in other dedicated reviews. [41,[46][47][48][49] In all cases OER involves multi-proton-coupled electron-transfer steps, suffering from the limitation of suboptimal scaling relation between OOH and OH adsorption energies, which is the major bottleneck and requires a cell potential above 1.23 V. [7] In biomass electrolysis, a complete oxidation process, also known as electrochemical reforming, such as methanol electrolysis, produces CO 2 under acidic condition (CO 3 2− under alkaline) in the anode and H 2 at the cathode, resulting in a maximum proton utilization. The partial oxidation of certain feedstocks could concomitantly generate H 2 and value-added chemicals.…”
Section: Water and Biomass Electrolysis Comparisonmentioning
confidence: 99%
“…Currently, progress has been made in utilizing cheaper earth-abundant metals in both substrates and electrocatalysts, with Ni-based multimetallic catalysts exhibiting considerable performance in both OER and HER reactions . Our attention here is particularly toward NiFe layered double hydroxides (LDH), whereby a considerable number of studies have reported its use as an effective OER electrocatalyst. NiFe LDH has been reportedly synthesized by using solvothermal, coprecipitation, and electrodeposition methods and demonstrated satisfactory performances of around 260–350 mV overpotential at 10 mA/cm 2 with reported OER operational stability of 10 h and beyond.…”
Section: Introductionmentioning
confidence: 99%